Human Resource Shortage in H. Bachtiar Djafar Skit Hospital: Challenges and Solutions - Wulan Dwi Citra Sari; Mutia Friska; Putri Adinda Ramadhani Hutagalung; Fhidiana Sari; Jihan Mawaddah Pane; Husnida Putriyana Hutabarat; Romiza Arika (PROMOTOR, 2026)
Hospitals are public facilities owned by the government or private sector and play a crucial role in improving the quality of public health services. The quality of health services is crucial for assessing how well a hospital provides services to patients. In addition, this study aims to provide strategic suggestions for addressing the problem of energy shortages so that healthcare services in hospitals can run better and more sustainably. The research method used is a qualitative research method using a case study approach to explore in depth the constraints of human resource shortages at H. Bachtiar Djafar Hospital. The results of this study state that the shortage of human resources at H. Bachtiar Djafar Hospital is influenced by the uneven distribution of health workers, geographical factors, suboptimal quality of human resources, and policy and bureaucratic limitations, more strategic human resource management efforts and continuous policy support are needed to overcome these challenges. This study concludes that a letter has been submitted to the Medan City Government for additional medical personnel and network collaboration with various agencies. However, challenges such as limited health worker quotas and urgent needs in various service facilities make this human resource problem still a major focus that requires sustainable and strategic solutions in hospital human resource management.